2018
DOI: 10.1145/3159172
|View full text |Cite
|
Sign up to set email alerts
|

Mean-Field Analysis of Coding Versus Replication in Large Data Storage Systems

Abstract: We study cloud storage systems with a very large number of files stored in a very large number of servers. In such systems, files are either replicated or coded to ensure reliability, i.e., to guarantee file recovery from server failures. This redundancy in storage can further be exploited to improve system performance (mean file-access delay) through appropriate load-balancing (routing) schemes. However, it is unclear whether coding or replication is better from a system performance perspective since the corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…al. address this problem by a form of mean field analysis, whereby any fixed number of queues are assumed to be independent of each other as the number of servers goes to infinity [21]. Simulation results support the validity of the independence assumption, and the mean-field approach certainly looks worthy of further investigation in large scale cloud systems, for example.…”
Section: Related Workmentioning
confidence: 85%
“…al. address this problem by a form of mean field analysis, whereby any fixed number of queues are assumed to be independent of each other as the number of servers goes to infinity [21]. Simulation results support the validity of the independence assumption, and the mean-field approach certainly looks worthy of further investigation in large scale cloud systems, for example.…”
Section: Related Workmentioning
confidence: 85%
“…Two well studied file encoding strategies used in distributed systems with redundant storage are MDS coding [10], [23], [34], [42] and replication [19]- [21], [24]. It has been shown that MDS coding outperforms replication in mean file access latency [4], [10], [44].…”
Section: A Related Workmentioning
confidence: 99%
“…We can compute the sum of mean number of useful servers aggregated over first V (1 − β) downloads. 4 Theorem 6: Consider the heterogeneous B server system with download rates μ b defined in Eq. ( 30), under the random (B, V, R) replication storage defined in Definition 7 and random scheduling defined in Definition 9.…”
mentioning
confidence: 99%
“…We assume that the read and the write requests for the file arrive as Poisson processes with rates λ r and λ w respectively. This is a widely accepted model for arrivals in distributed storage [11], [14], [22] and caching systems [23]- [25]. This assumption is motivated by analytical tractability, and the fact that this is a good approximation for the arrivals [26]when a large number of independent clients are reading from and writing to the system.…”
Section: A Arrivals Of Read/write Requestsmentioning
confidence: 99%